Effectiveness of Automated External Defibrillator Drones for Handling Out-Of-Hospital Cardiac Arrest (OHCA): Literature Review - Nurhayati, Nurhayati; Roswita, Ria (Midwifery and Nursing Research, 2024)
Background: Out-of-hospital cardiac arrest is one of the leading causes of death worldwide. Out-of-hospital cardiac arrest or OHCA represents a significant burden of disease globally. The number of out-of-hospital cardiac arrests reaches 360,000 events every year. Treatment for cardiac arrest requires immediate defibrillation to increase the survival rate of OHCA patients. One method that can be used is by sending AEDs using drones. It is hoped that sending and using AEDs via drones can increase the rate of AED application and reduce defibrillation time.Methods: This study is a literature review which aims to determine the effectiveness of AED drones for treating out-of-hospital cardiac arrest (OHCA). This literature review analyzes 10 articles originating from journal databases, namely Google Scholar, Pubmed and Science Direct with the keywords "Drone AED", "EMS". And “Out-Of-Hospital Cardiac Arrest”.Results: The results of the analysis show that AEDs delivered with an Unnamed Aerial Vehicle (UAV) system using drones can reduce the time for administering defibrillation immediately before health workers arrive. Success in treating OHCA and a higher chance of life, AED delivery by drone can also save costs. to send an EMS ambulanceConclusion: Based on the results of the analysis of several articles, it was concluded that AED drones were effective in delivering AEDs in cases of Out-Of Hospital Cardiac Arrest (OHCA) which occurred in remote areas or far from public locations. AEDs delivered using an Unnamed Aerial Vehicle (UAV) system using drones can reduce the time to provide defibrillation immediately before health workers arrive, resulting in success in treating OHCA and a higher chance of life. AED delivery by drone can also save the costs required to send an EMS ambulance. However, there are several obstacles that can be found from several articles, namely that sending AEDs requires a flight permit from the government, the design of drones for AEDs must be appropriate, and in bad weather sending AEDs by drone can be hampered. Therefore, further research needs to be carried out to provide a solution for sending AED drones during extreme weather.